Theologies of the American revivalists : from Whitefield to Finney - Caldwell, Robert W. (Downers Grove : InterVarsity Press, 2017)
For centuries, revivals--and the conversions they inspire--have played a significant role in American evangelicalism. Often unnoticed or unconsidered, however, are the particular theologies underlying these revivals and conversions to faith. With that in mind, church historian Robert Caldwell traces the fascinating story of American revival theologies from the First Great Awakening through the Second Great Awakening, from roughly 1740 to 1840. As he uncovers this aspect of American religious history, Caldwell offers a reconsideration of the theologies of figures such as George Whitefield, Jonathan Edwards, John Wesley, Joseph Bellamy, Samuel Hopkins, and Charles Finney. His scope also includes movements, such as New Divinity theology, Taylorism, Baptist revival theology, Princeton theology, and the Restorationist movement. With this study, we gain fresh insight into what it meant to become a Christian during the age of America's great awakenings. --
Moderate evangelical revival theology in the first great awakening -- First great awakening alternatives: the revival theologies of Andrew Croswell and Jonathan Edwards -- Revival theology in the new divinity movement -- Congregationalist and new school Presbyterian revival theology in the second great awakening -- Methodist revival theology in the second great awakening -- Revival theologies among early American Baptists -- The new measures revival theology of Charles Finney -- Two responses to modern revival theology: Princeton Seminary and the restoration movement.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher; resource not viewed.
Master record variable field(s) change: 072 - OCLC control number change
Keywords: Great Awakening; Religious awakening -- Christianity; United States -- Church history; Revivals -- United States -- History; Reformed Church -- Doctrines -- History; Great Awakening; Reformed Church -- Doctrines; Religious awakening -- Christianity; Revivals; United States; RELIGION / Christianity / History; Church history; History; Electronic books